A test of famine-induced developmental programming in utero. (5th November 2018) - Catalano, Ralph; Gemmill, Alison; Bruckner, Tim
Abstract: The 'DOHaD' literature argues that stressors encountered at age t 'program' individual health at age t+n, and that this programming appears strongest when t defines critical developmental periods including gestation. Accordingly, children of ill-nourished pregnant women suffer greater later life morbidity than do offspring of well-nourished mothers. The possibility that circumstances other than access to nutritious food drive both a mother's diet and fetal development remains, however, a threat to the inference of programming in utero . Attempts to rule out this threat include tests of the hypothesis that birth cohorts in gestation during famines exhibit shorter life spans than other cohorts. The tests produce conflicting results attributed to confounding by autocorrelation, selective migration and introduction of modern medicine. We offer a test in which neither medicine nor migration nor autocorrelation could obscure the presumed effect. We apply time-series regression methods to the life span of Swedes born between 1751 and 1800 to test the hypothesis that cohorts exposed in utero to the Swedish Famine of 1773 lived shorter lives than expected from trends and other forms of autocorrelation. We use these 50 birth cohorts not only because they included those exposed to severe famine but also because they may well be the only human birth cohorts that completed life unaffected by selective migration and unaided by modern medicine and for which we know life span. We find that the cohort born in 1773 live 4.2 years longer than expected from trends over the last half of the 18th century.